Time on teaching task and perceived instructional needs of practicing nursery and primary school teachers of English language (2011)
The study examined ‘Time on Teaching Task’ as determinant of perceived instructional needs of nursery and primary school teachers while planning and teaching English language lessons as well as marking teaching English assignments. Good acquisition of pedagogical skills in this subject area could lead to preschool children’s effective understanding of this subject and better achievement in other subject areas. Subjects were 486 nursery and primary school teachers in Oyo state (Nigeria) who were requested to respond to a 2Qdtem need assessment questionnaire and provide personal information on age, gender, teaching experience, and the amount of time spent planning, teaching and marking pupils assignments in this subject area. Data analysis was done using the chi-square and multiple regression statistics. The result revealed that ‘Time spent on marking Task’ is a major determinant of perceived instructional needs of teachers while class size played a significant role in determining the amount of time spent. In particular, teachers tended to spend most of their teaching periods ‘marking pupils assignment in the subject than the amount of time spent ‘teaching’ and ‘planning instructions respectively. The finding seems to suggest that teachers who spend more time to regularly mark pupils assignments perceived less needs for improved instruction. On the strength of the findings, three educational implications were identified. Finally, the need to replicate the study in other states within the country was emphasized.